Beyond Watt Market Roundabout Audiences: Redesigning Tourists Oriented Theatres in Calabar - Yta, Edisua Merab (Jurnal Office, 2020)
Â Calabar, a coastal town in South-South Nigeria, has had a long-standing history of cultural tourist-oriented theatre performances. And today, its image as a tourist city has grown in leaps because of the Christmas Festival (A 32-day entertainment art and cultural events) it hosts annually plus other tourism products or attractions that complement the festival. Carnival seems to be a major attraction. Other attractions are not emphasized. This study explored how tourism-oriented theatres can be developed to add to existing attractions and increase varieties for tourists. The study used a combination of research methods including experiential theatre performances, participant observation, and focus group discussion. Findings show that local culture and arts and creative industries i.e., theatre can be used to promote destinations and enhance their attractiveness. They can help build the image of the city and promote indigenous arts and culture. This research significantly models the utility of theatre in the service of tourism and urban development. Some key recommendations this research makes include, the collaboration of the tourism industry, the performing arts sectors, and private business owners. Creating demand and market for specially packaged theatre products for tourists working with travel agencies to ensure that theatre is taken from the mainstream to the tourists.